Performance evaluation of telecommunication services provision with combined approach of balanced scorecard and system dynamics (case study: telecommunications infrastructure company). (17th June 2021) - Nahavandi, Nasim; Bakhshi, Nastaran
One of the prerequisites for developing telecommunications industry is continuous performance evaluation. Despite the popularity of balanced scorecard approach (BSC), it has some limitation such as lack of a systematic perspective, not considering the dynamic relationships between indicators and delays. The purpose of this paper is to present a system dynamics (SD) model along with BSC to evaluate the performance of the telecommunications infrastructure company (TIC), the sole custodian of telecommunications networks in Iran. This is the first work that dynamics of TIC is investigated and the performance of TIC is evaluated by combined approach of BSC and SD. In the process of modelling, and according to experts, the indicators of International Transit Capacity and R&D investment are added to the existing indicators in the literature. Finally by determining the leverage points and simulating different policies, the best policies are presented.